Analisis Faktor Yang Mempengaruhi Perusahaan Sektor Perbankan Melakukan Pergantian Kantor Akuntan Publik Periode 2019-2023 - Maria Anjeli Hutagaol; Duma Megaria Sihite; Nia Angelia (Politeknik Raflesia Press, 2025)
This research aims to determine the analysis of factors that influence banking sector companies in changing public accounting firms. The type of data used in this research is secondary data in the form of annual financial reports (annual reports) from companies listed on the Indonesia Stock Exchange (IDX). The research method uses descriptive statistical analysis and logistic regression analysis with a population of 40 banking companies listed on the Indonesia Stock Exchange (IDX). Purposive sampling resulted in 16 companies that met the sample criteria using the purposive sampling method. The data obtained was then processed using IBM SPSS 26 analysis tool. The results of this study indicate that partially management change does not significantly influence the change of public accounting firms. Similarly, company growth does not significantly influence the change of public accounting firms, and company size research also does not significantly influence the change of public accounting firms. The independent variables influence the change of the dependent variable by 7.5% and the remaining 92.5% is influenced by other variables outside the research.